Lifelong Learning and Education as a Basis for the Quality of Life of Pedagogical Workers (Journal of Universal Excellence, 2026)
Research question: How do pedagogical workers use life-long learning to educate themselves during their active working life?Purpose: The aim of the article is to determine the relationship between the working environment, family and the life-long learning for adults.Method: Desk research. Descriptive analysis of theory and quantitative method of research through an on-line survey.Results: Individuals must provide opportunities for education and learning (financial resources, support of the partner/family, etc.).Organisation: Despite their knowledge and skills, adults should be involved in life-long learning and education since this is the basis of the quality of life of each individual.Society: The involvement of pedagogical workers in life-long learning is important from the point of view of the individual and the society in general - especially since it possesses knowledge and gained experience. From this point of view, they can be socially beneficial and above all a good foundation for intergenerational socialising in the field of knowledge and education.Originality: The research is important for the Slovenian social space and determines the importance of life-long learning during the active working period.Restrictions / further research: The questionnaire was distributed to active pedagogical workers who often face obstacles when choosing additional and further education (time, family, financial resources, distance from the place of education and learning). For further research, we propose a comparative study of the possibilities of learning and education of adult employees with one neighbouring country.
Keywords: work; learning; life-long learning; education; obstacles